Can Research Contribute to Improve Educational Practice?. (2020) - Ferrero, Marta
Abstract: Teaching a diverse classroom is a challenging task. Educators are faced daily with the difficult task of making many decisions about how to educate each of their students. To do this, they mainly rely on their experience and that of their colleagues, their values, and thoughts. Although they are inherent and important in the profession of teaching, sometimes these resources may not suffice to make the best decisions, particularly when teachers are continuously bombarded with numerous fads and poorly grounded ideas about education. In this context, research-informed practice emerges as a promising approach. It involves integrating the professional expertise of teachers with the best evidence of researchers to make better decisions and improve education. However, for this approach to be successfully implemented, the gap between researchers and practitioners must first be bridged. The possible solutions to this challenge involve acting in three contexts: research production, research communication and research use. Specific measures in each of these contexts are described.